TECHNICAL EFFICIENCY OF UPLAND RICE FARMERS IN MAKURDI LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA USING A STOCHASTIC FRONTIER MODEL - Ogah, O.M.; Iorlamen, T.R.; Benjamin, B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined efficient utilization of resources for upland rice production in Benue State, Nigeria. A three-stage multi stage random sampling technique was used to select 120 respondents for the study. Data was obtained from primary source with the use of well-structured questionnaire and analysed using stochastic production frontier. Results showed the variance parameter sigma squared (δ2) to be 0.1375, significant at the 1% level, suggesting a possible degree of inefficiency among the upland rice growers. Increased use of fertilizer (0.001985) and seed (0.06299) will enhance rice yield, according to the elasticity coefficient, which showed that both parameters were positive and significant at the 1% and 5% levels, respectively. Age (-0.7153), household size (0.4212), and credit availability (-0.123) all had negative coefficients and significant effects on technical efficiency results at 5% and 1% level respectively; these variables increase farmer’s technical efficiency and decreases technical inefficiency. The mean technical efficiency was 84%. The study concludes that farmers were operating below the frontiers and recommend provision of credit to farmers to stimulate their efficiency, inputs like improved rice seeds and fertilizer should be made available to the farmers at subsidized rate, policies to encourage farmer’s participation in rice farming should be deployed.